2000
DOI: 10.1074/jbc.c000276200
|View full text |Cite
|
Sign up to set email alerts
|

The Breast Cancer Susceptibility Gene BRCA1 Is Required for Subnuclear Assembly of Rad51 and Survival following Treatment with the DNA Cross-linking Agent Cisplatin

Abstract: Germ line mutations in BRCA1 or BRCA2 genes result in a marked increase in the risk of early onset breast and ovarian cancers (5-10). BRCA1 and BRCA2 appear to have multiple functions including roles in transcriptional regulation (11)(12)(13)(14) and cell cycle checkpoint control (15)(16)(17)(18)(19)(20).1 Brca1 and Brca2 both have transcription activation functions (11, 13); Brca1 co-activates transcription with p53 (21,22). Recently it has been demonstrated that Brca1 participates in homologous recombination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
368
1
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 540 publications
(391 citation statements)
references
References 62 publications
17
368
1
5
Order By: Relevance
“…Therefore, these tumours show high sensitivity to platinum-based chemotherapy, both in vitro [96][97][98] and in vivo. [99][100][101] Previous studies in ovarian cancer suggested that mutations in both genes were associated with similar responses to platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these tumours show high sensitivity to platinum-based chemotherapy, both in vitro [96][97][98] and in vivo. [99][100][101] Previous studies in ovarian cancer suggested that mutations in both genes were associated with similar responses to platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 is essential for HR repair and the recruitment of RAD51 to repair foci. 37,38 We therefore measured the efficiency of HR in cells using the DR-GFP reporter assay under conditions where the recruitment of 53BP1 and BRCA1 into IRIF was blocked. 39 U20S cells containing an integrated copy of the DR-GFP reporter were transduced with lentivirus encoding mCherry as a control, or mCherry-tagged RAD18 WT, RAD18 D221A, or RAD18 UBZ domain, and we measured the ability of mCherry-positive cells to express GFP protein following expression of the I-SceI endonuclease.…”
Section: Ectopic Expression Of Rad18 Inhibits Recruitment Of 53bp1 Bmentioning
confidence: 99%
“…This led to the proposal that BRCA1 and BRCA2 function in daughter strand gap repair [11,28]. Efficient Rad51 focus formation at DSBs induced by laser scissors or ionizing radiation (IR) is dependent upon BRCA1 and BRCA2, and Rad51 retention on chromatin following HU treatment is impaired in the absence of wild-type BRCA2, suggesting a possible role for BRCA1 and 2 in loading Rad51 onto ssDNA [97][98][99][100]. Lomonosov et al visualized replication structures in rDNA of BRCA2 mutant mouse embryonic fibroblasts (MEF) during HU treatment.…”
Section: Role Of Brca1 and Brca2 In Hr Regulationmentioning
confidence: 99%